Diagnosis and management of children with Blue Rubber Bleb Nevus Syndrome: A multi-center case series. Issue 11 (November 2019) - Isoldi, Sara; Belsha, Dalia; Yeop, Intan; Uc, Aliye; Zevit, Noam; Mamula, Petar; Loizides, Anthony Meneloas; Tabbers, Merit; Cameron, Don; Day, Andrew S.; Abu-El-Haija, Marwa; Chongsrisawat, Voranush; et al.
Abstract: Background: Blue Rubber Bleb Nevus Syndrome (BRBNS) is a rare, severe, sporadically occurring disorder characterized by multiple venous malformations. Aims: To present and analyze a case series of pediatric patients with BRBNS and to describe diagnostic approaches and management options applied. Patients and methods: Multicenter, retrospective study, evaluating the diagnosis and management of children with BRBNS. Results: Eighteen patients diagnosed with BRBNS were included. Cutaneous venous malformations were observed in 78% and gastrointestinal venous malformations in 89%. Lesions were also found in other organs including muscles, joints, central nervous system, eyes, parotid gland, spine, kidneys and lungs. Gastrointestinal lesions were more common in the small intestine than in stomach or colon. The management varied significantly among centers. Endoscopic therapy and surgical therapy alone failed to prevent recurrence of lesions. In younger children and in patients with musculoskeletal or other organ involvement, sirolimus was used with 100% success rate in our series (5 patients treated) although poor compliance with subtherapeutic sirolimus trough levels led to recurrence in a minority. Conclusions: Considering the multi-organ involvement in BRBNS, diagnosis and management requires a multidisciplinary approach. The treatment includes conservative, medical, endoscopic and surgical options. Prospective multicenter studies are needed to identify the optimal management of this rare condition.